Tissue temperature estimation in-vivo with pulse-echo - Maass-Moreno, Roberto; Sanghvi, Narendra T.; Damianou, Christakis A. (My University, 1995)
Time-shifts between echoes from volumes of tissue heated with focused ultrasound has been shown to track temperature changes accurately in-vitro. In this study we report the application of this method in-vivo where motion and perfusion have an additional effect on the measured shifts. Motion was characterized by the time-shifts detected on an echo segment from a proximal non-heated tissue site and a correction was applied to minimize their effect. The delay vs. temperature relationship (δ(T)) was similar to that previously described in-vitro but parameter variations were larger. Unlike in-vitro, the mean dδ/dT during temperature increases differs some from that during the cooling phases. It is suggested that this behavior can be predicted from the characteristics of the irradiating transducer and the acoustic parameters of the tissue and incorporated to the delay detection procedure.
Keywords: Temperature; In vitro; Delay; Ultrasonic imaging; Motion measurement; Ultrasonic variables measurement; Motion detection; Acoustic signal detection; Cooling